RENCANA DESIGN TEMPAT WUDHU MASJID MIFTHAHUL KHAIR KELURAHAN LAOMPO - Efendi, Ahmad; SR, Hendra Kundrad; Ardianti, Wa Ode Vicky (MAJU : Indonesian Journal of Community Empowerment, 2025)
The Mifthahul Khair Mosque has ablution facilities that are not adequate in terms of comfort, cleanliness, and ease of access. The community service carried out aims to design ablution venue facilities that are in line with Islamic architectural values, ergonomic principles, and environmentally friendly development concepts. The method of service carried out begins with initial coordination with the mosque administrator, then field surveys and data collection, then literature review and comparative studies of various designs of mosque ablution places are carried out, then the preparation of technical designs of ablution temples is carried out, then design validation is carried out to the mosque administrators, and finally documentation and submission of the design of the ablution place to the mosque administrators. The result is a complete ablution facility design document with plans, appearances, cuts, material specifications, drainage systems, cost estimates, and designs that promote privacy, security, water efficiency, and access for users. This activity not only produces applicable technical solutions, but also increases public awareness of the importance of efficient and sustainable planning of worship spaces.